Development of Kinemaster Video in Learning Social Science in Grade 4 at SD Negeri Kauman 2 - Sutrisno, Nanang; Fatirul, Achmad Noor; Fiantika, Feny Rita (UNDIKMA, 2025)
This research is a development study using the Kemp Instructional Design Model, aimed at creating KineMaster-based learning videos on the topic of Hindu and Buddhist kingdoms for Grade 4 IPAS learning. The development process involved validation from design, material, and media experts, as well as peers. Product testing was conducted in three stages: small, medium, and large group trials. Data were collected using questionnaires to assess aspects such as content clarity, accessibility, and engagement. The results show that KineMaster videos improve student interest and understanding, especially for abstract or difficult topics. The combination of visuals and audio helps make learning more interactive and enjoyable. Additionally, students can access the material anytime, supporting flexible learning. For teachers, KineMaster enables more creative content delivery and offers opportunities for students to participate in creating learning media. However, some challenges remain, such as limited technical skills and the time required to produce high-quality videos. Therefore, training for both teachers and students is important to maximize the benefits of this technology. In conclusion, KineMaster-based videos are a promising tool to enhance learning quality, increase student motivation, and foster creativity in the classroom.